Davidson and classical pragmatism - Rossi, Paula (Areté, 2007)
In this paper I wish to trace some connections between Donald Davidson's work (1917-2003) and two major representatives of the classical pragmatist movement: Charles S. Peirce (1839-1914) and William James (1842-1910). I will start with a basic characterization of classical pragmatism; then, I shall examine certain conceptions in Peirce's and James' pragmatism, in order to establish affinities with Davidson´s thought. Finally, and bearing in mind the previous con-nections, I will reflect briefly on the relevance –often unrecognized- of classical pragmatist ideas in the context of contemporary philosophi-cal discussions.